1998
DOI: 10.1007/s004240050747
|View full text |Cite
|
Sign up to set email alerts
|

A regional gradient of cardiac intrinsic rhythmicity depicted in embryonic cultured multiple hearts

Abstract: We used optical methods to examine the spatial gradient of intrinsic rhythmicity in early-stage multiple-heart chick embryos. The latter were induced experimentally in whole-embryo culture. The embryos were cut microsurgically through the tissue of the anterior intestinal portal at the 5- to early 7-somite developmental stage. Spontaneous electrical activity in 4 to 6 segmented hearts, during the 7- to 10-somite stages of development, were monitored simultaneously by means of multiple-site optical recordings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…This process can be considered as "selforganization", and also as a process of emergence of an ordered functional structure [2]. We have pointed out that the organization of the cardiac pacemaking area during the ontogenetic development can be regarded as an example of functional self-organization [11]. A definitive conclusion requires further studies.…”
Section: In Vitro Model Of Macro Reentrymentioning
confidence: 98%
“…This process can be considered as "selforganization", and also as a process of emergence of an ordered functional structure [2]. We have pointed out that the organization of the cardiac pacemaking area during the ontogenetic development can be regarded as an example of functional self-organization [11]. A definitive conclusion requires further studies.…”
Section: In Vitro Model Of Macro Reentrymentioning
confidence: 98%
“…Studies of the early electrical activity of the heart in the 1970s and early 1980s showed that cardiomyocytes exhibit small patterns of electrical activity before they contract [ 35 , 36 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ]. The TTX receptor and the fast Na + channel machinery have been shown to exist even when APs are insensitive to TTX (3 day old embryos, HH stage 20) [ 152 ].…”
Section: Electrodes and Application To Study Cardiogenesismentioning
confidence: 99%
“…To establish this concept, we have been carrying out a series of experiments that use congenital and experimentally produced embryonic chick double-hearts at the prebeating stages or just after the onset of beating, and we demonstrated the left-side dominance of pacemaking activity during these stages [90][91][92]. Recently, we further demonstrated a cephalo-caudal gradient with caudal dominance of pacemaker activity by using cultured embryonic chick multiple-hearts produced by microsurgical techniques [93].…”
Section: Early Embryonic Heartsmentioning
confidence: 99%